The Bill of Rights in Modern America Third Edition, Revised and Expanded. - Bodenhamer, David J. (Indiana University Press, 2022)
--A newly revised and updated version of the 2008 revised edition with updated introduction, four new chapters. --The editors were encouraged to update this edition with issues of diversity in mind. They have done so by including the expertise of more women and people of color. Also includes suggestions for further reading. --The audience for the work is primarily scholarly, though the work does lend itself to classroom discussion and course adoption as well. Readers would include legal scholars, legal anthropologists, and those who work in issues of modern rights and social justice.